Navigating Education in the Context of COVID-19 Lockdowns and School Closures: Challenges and Resilience Among Adolescent Girls and Young Women in South Africa - Duby, Zoe; Jonas, Kim; Bunce, Brittany; Bergh, Kate; Maruping, Kealeboga; Fowler, Chantal; Reddy, Tarylee; Govindasamy, Darshini; Mathews, Catherine (Frontiers in Education, 2022)
Gender related vulnerabilities and inequalities place female learners at high risk of school disengagement due to COVID-19 disruptions. Understanding the impacts of school closures and educational disruptions on female learners in South Africa is critical to inform appropriate, gender-sensitive policies and programmes, to mitigate further exacerbation of educational inequalities. We examined the effects that COVID-19 and lockdowns have had on the educational experiences of adolescent girls and young women (AGYW) aged 15-24, in six districts of South Africa characterised by high rates of HIV, teenage pregnancy and socio-economic hardship. Following a concurrent triangulation mixed-methods approach, we conducted a cross-sectional survey with 515 AGYW, and qualitative interviews with 50 AGYW. More than half of survey participants enrolled in education had been unable to continue with their studies. Factors associated with educational disruption included low socio-economic status, lack of cell phone access and household food insecurity. Qualitative narratives included challenges with online learning and studying at home in resource restricted settings, and insufficient support from schools and teachers. However, despite multiple barriers to continuing education, some AGYW demonstrated educational resilience, enabled by psychosocial and structural support, and resource access. Our findings lend support to an emerging evidence base showing that the closure of schools and tertiary institutions, combined with challenging home environments, and a lack of access to appropriate technology, has disproportionately impacted the most vulnerable AGYW, exacerbating pre-existing educational inequalities within the South African education system. Addressing structural barriers to educational equity, particularly in the pandemic context, including access of technology and the internet, is urgent.